Empirically comparing information systems outsourcing with end-user computing development. (11th May 2004) - Udo, Godwin J.
The two most popular techniques for managing information technology are outsourcing and end-user computing development (EUCD). The benefits and drawbacks of each technique have been cited in the literature respectively by their proponents and opponents. The present study set out to compare the effectiveness of the two techniques based on their potential benefits and drawbacks. A survey of 97 US firms provided the data for the comparison. The findings indicate that EUCD appears to be a better technique than outsourcing in eight out of the ten benefits considered. There was no significant difference between the two techniques in the case of the remaining two benefits (increased IT/worker utility and system flexibility). Secondly, no significant difference in drawbacks was found between the two techniques. These findings contradict the claims of the outsourcing vendors but confirms the findings of some authors. A study of this nature has some important implications to the practitioners in today's economy that competitive advantage is based, in large part, on a firm's capability to acquire and use quality information with its information technology resources at the least possible cost.